Merging with the metals: an analysis of the role micro-political relationships played in the merger of the Printing and Kindred Industries Union with the Australian Manufacturing Workers Union. (3rd September 2019) - Blissett, Ed
ABSTRACT: In the spring of 1987, the Printing and Kindred Industries Union (PKIU), Federal Executive Committee, reluctantly concluded that membership decline and the resultant fall in income meant that the union needed to find an amalgamation partner. In common with many Australian unions, which felt similarly compelled to merge, there was initially a lack of consensus over a preferred merger partner. In most other unions these disagreements were eventually resolved, an amalgamation deal negotiated, and membership endorsement of the merger secured. This was not the case in the PKIU. Instead the union remained in intense internal conflict, throughout the seven-year amalgamation process. Scholars have suggested that the PKIU's amalgamation fissures were caused by political, economic, industrial and institutional disagreements. Other authors have gone further and argue that dramatic shifts in the PKIU's and other unions amalgamation policies, during the 1980s and 1990s, were the result of alterations in the strengths of different internal political factions, or the rejection of a union's merger policy by the membership. This article, while accepting that political, economic, industrial and institutional factors all influenced the PKIU's internal debate, puts forward an alternative hypothesis. It asserts that micro-political factors, specifically personal animosities, friendships and loyalties, played a significant role in determining the eventual choice of an amalgamation partner, and the contrasting results of its two merger ballots.